Panel Export Taxes (PET) dataset: New data on export tax rates - Olga Solleder (Graduate Institute of International and Development Studies, 2013)
This paper describes a newly collected dataset on export tax rates, which provides comprehensive coverage for 20 countries, 2 time periods and all products at HS6 level. Export tax rates are based on national government documentation, including preferential provisions for partner countries. The data are organized in a harmonized and comparable format, including ad-valorem equivalents of specific taxes. The dataset can contribute to the empirical analysis of export taxes - an increasingly applied trade policy instrument, which merits further attention from academia and policy makers alike. Furthermore, the paper contains literature review and stylized facts highlighting various aspects of export taxes.
Keywords: C81; F13; F42; H21; Y10; 330; export taxes; trade taxes; taxation of exports; export levies; export duties; export tax rates; export tax data; export tax agreements; export restrictions; Exportsteuer; Handelseffekt; WTO-Regeln; Panel; Gravitationsmodell; Welt